The Effectiveness of Cognitive Behavioral Therapy on Increasing of Self-Efficacy and Improving of Addiction Symptoms among Drug Dependency Patients - Hamid Kamarzarin; Hosin Zaree; Hosin Brouki, M (Drug Control Headquarters, Research and Education Office, 2012)
Introduction: The aim of this study was to determine the effectiveness of cognitive behavior therapy on increasing of self efficacy and improving of addiction symptoms among drug dependency patients. Method: For this purpose, 90 substance abusers were selected of private addiction center, Central Prison and drop in center by using of random sampling, and they were divided into two experimental (45 subjects) and witness groups (45 subjects) randomly. The members of experimental group were under 12 sessions of cognitive behavioral therapy by Carol method, and control group only have taken Methadone and other physical drugs. All participants at the beginning of research, during the study (after three months) and three months after treatment completed self-efficacy questionnaire and Maudsley addiction profile (Map) by a psychologist were assessed. The symptoms of addiction recovery and addiction treatment process. Results: Analysis of covariance indicated the treatment effectiveness and its maintenance on increasing of efficacy and reducing of the symptoms of Maudsley addiction profile. Conclusion: Cognitive behavior therapy is effective to increase self-efficacy and improve symptoms in substance abusers.